Analysis of depression in rural empty-nesters and coping strategies (我国农村空巢老人抑郁现状影响因素分析及应对策略研究) - (曾乙明); LI Shenmei (李神美); WANG Miyuan (王蜜源) (Association of Integrative Nursing, 2022)
Objective To investigate the current status of depression and related influencing factors among rural empty-nesters in China, and to provide some theoretical basis and suggestions for further improving the health management of the elderly in China to ensure healthy Ageing. Methods Rural empty-nesters aged 65 years and above were selected from the subjects was measured by a short version of the Center for Streaming Depression Scale ( CES-D10 ), and the factors influencing depressive symptoms in rural empty-nesters were explored by statistical methods of logistic regression analysis. Results Totally 1578 rural empty-nesters over 65 years of age scored (8. 9 ± 6. 7) on the CES-D10 scale; 966 (61. 22%) had no depressive symptoms and 612(38. 78%) had depressive symptoms. The differences in life satisfaction, self-rated health status, gender, education level, marital status, presence of pension insurance, nighttime sleep duration and economic income status were statistically significant (P＜0. 05). logistic regression analysis showed that life satisfaction, self-rated health status, gender, nighttime sleep duration and economic status had some influence on depressive symptoms among rural empty-nesters (P＜0. 05). Conclusion The detection rate of depressive symptoms among rural empty-nesters in China is still at a high level, and mental health prevention and care measures should be increased to ensure healthy ageing for people with low life satisfaction, poor self-rated health status, low education level, no pension insurance and low economic income. (目的 调查我国农村地区空巢老人抑郁现状与相关影响因素, 为进一步改善中国老年人健康管理提供一定理论依据及建议, 以保障健康老龄化。方法 从 2018 CHARLS数据库中选取 65 岁及 65 岁以上的农村空巢老人为调查研究对象( n=1578)。通过简版的流调中心抑郁量表(CES-D10)来测定受试者的抑郁状态情况, 并通过Logistic回归分析的统计学方法来探讨影响农村空巢老人抑郁症状的因素。结果 1578例 65岁以上农村空巢老人CES-D10量表得分为(8. 9 ± 6. 7)分; 无抑郁症状966(61. 22%)例, 有抑郁症状612(38. 78%)例。其中生活满意度、自评健康状况、性别、受教育程度、婚姻状况、有无养老保险、夜间睡眠时长、经济收入状况差异具有统计学意义(P＜0. 05)。Logistic回归分析表明: 生活满意度、自评健康状况、性别、夜间睡眠时间和经济状况对农村空巢老人抑郁症状存在一定影响(P＜0. 05)。结论 我国农村空巢老人抑郁症状检出率仍处于较高水平, 应针对生活满意度低、自我评价健康状况差、受教育程度低、无养老保险、经济收入低等人群, 加大心理健康预防和护理措施, 确保健康老龄化。)